2017
DOI: 10.1186/s12964-017-0195-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage response and cancer therapeutics through the lens of the Fanconi Anemia DNA repair pathway

Abstract: Fanconi Anemia (FA) is a rare, inherited genomic instability disorder, caused by mutations in genes involved in the repair of interstrand DNA crosslinks (ICLs). The FA signaling network contains a unique nuclear protein complex that mediates the monoubiquitylation of the FANCD2 and FANCI heterodimer, and coordinates activities of the downstream DNA repair pathway including nucleotide excision repair, translesion synthesis, and homologous recombination. FA proteins act at different steps of ICL repair in sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 140 publications
(131 reference statements)
0
84
0
Order By: Relevance
“…Using the structure of the SAUGI/human UDG complex to explain the conserved binding strategy of SAUGI to UDGs. (Left) The UDG component of the human UDG/ DNA complex showing four functional motifs of human UDG: Water‐activating loop: 63‐QDPYH‐67 (blue), Pro‐rich loop: 165‐PPPPS‐169 (green), Gly‐Ser loop: 246‐GS‐247 (red), and Minor groove intercalation loop: 268‐HPSPLS‐273 (yellow). These motifs play important roles in the DNA substrate binding and glycosidase activity of UDGs .…”
Section: Recent Reports On Dmps (2014 To Present)mentioning
confidence: 99%
“…Using the structure of the SAUGI/human UDG complex to explain the conserved binding strategy of SAUGI to UDGs. (Left) The UDG component of the human UDG/ DNA complex showing four functional motifs of human UDG: Water‐activating loop: 63‐QDPYH‐67 (blue), Pro‐rich loop: 165‐PPPPS‐169 (green), Gly‐Ser loop: 246‐GS‐247 (red), and Minor groove intercalation loop: 268‐HPSPLS‐273 (yellow). These motifs play important roles in the DNA substrate binding and glycosidase activity of UDGs .…”
Section: Recent Reports On Dmps (2014 To Present)mentioning
confidence: 99%
“…[34][35][36] Research has shown that the inactivation of AKT results in dephosphorylation and activation of FOXO transcription factors, which is involved in mediating cell cycle arrest, DNA repair and apoptosis. The therapy approach of targeting CTCF seems to be promising for the treatment of PC by regulating the FoxO signalling pathway and further retarding cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there have been an increasing number of studies on the use of combination therapies to treat cancer using DNA repair mechanisms. [34][35][36] Research has shown that the inactivation of AKT results in dephosphorylation and activation of FOXO transcription factors, which is involved in mediating cell cycle arrest, DNA repair and apoptosis. 31,32 It would be feasible to make a combination therapy via DNA repair progression.…”
Section: Discussionmentioning
confidence: 99%
“…AP sites and cross‐linked bases are usually repaired by BER, NER and MMR pathways during pre‐replicative stages . In post‐replicative stages of cell cycle, recombination machinery plays a critical role in DNA repair and replication restart . The up‐regulation of recG wed in M. smegmatis during stationary phase/UV damage, and down‐regulation during H 2 O 2 /MMS stress, indicates that the protein may play an active role in post‐replicative (stationary phase) recombination events, that proceed though branched DNA intermediates.…”
Section: Discussionmentioning
confidence: 99%